Liability insurance for a multinational company - Hynek, Jan (2019)
This diploma thesis provides a deep look into the insurance and its functioning. Main focus of the thesis is to describe the diversification of the risks within the insurance industry, meaning what is happening between the insurance entities while providing the insurance coverage for large industrial companies. Thus, the thesis will be mostly written from the insurance and reinsurance companies point of view. In order to simulate the ties between the insurance parties, I will also write about reinsurance – significant segment within the insurance. Particular process of insuring a company on a multinational level will be broadly discussed. Besides the process of insurance explanation, I will explain liability as a line of business of the insurance companies. This thesis should provide the understanding of how liability insurance works and shall serve as an example how insurance entities proceed and cooperate while providing coverage for a large industrial company.